Antimicrobial Potential and HPLC Analysis of BGR-34: An Antidiabetic Ayurvedic Formulation - Sharma, Anuj Kumar; Murti, Yogesh; Yadav, Sachdev; Ved, Akash; Sharma, Ketan; Kulshreshtha, Mayank (Anti-Infective Agents, 2026)
IntroductionBGR-34, a polyherbal formulation, has garnered attention for its antimicrobial properties, attributed to its diverse composition of primary and secondary metabolites.ObjectiveThe objective of the study was to generate good scientific data regarding BGR-34.MethodsThis study was carried out to investigate the phytochemical screening, High Performance Liquid Chromatography (HPLC) analysis used Quercetin as a standard, and antimicrobial efficacy of BGR-34 against significant human pathogens, including Klebsiella pneumoniae, Vibrio cholerae, Staphylococcus epidermidis, Listeria monocytogenes, Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, Salmonella typhi, Streptococcus mutans, Streptococcus pyogenes, Enterococcus faecalis, Bacillus subtilis, and Xanthomonas oryzae.Results and DiscussionThe findings revealed a dose-dependent antimicrobial effect, with optimal activity observed at 100 mg/mL, highlighting its potential as a therapeutic agent. The phytochemical screening confirmed the presence of various primary and secondary metabolites, such as flavonoids, alkaloids, saponins, carbohydrates, alkaloids, tannins, proteins, terpenoids, etc. HPLC analysis demonstrated the presence of quercetin (2.2974 ug/mL), which is responsible for various pharmacological activities. Antimicrobial potential showed activity of BGR-34 against various microbes that are responsible for various diseases. The bioactive compounds in BGR-34, such as phenolics, flavonoids, and terpenoids, exhibit mechanisms like biofilm disruption and microbial membrane interference, underscoring its broad-spectrum efficacy. Furthermore, its potential role in addressing infections related to biofilm-forming pathogens and resistant strains establishes its clinical significance.ConclusionThese results support the continued exploration of BGR-34 as a viable option in combating microbial infections, with implications for managing resistant pathogens, and reducing the burden of infectious diseases.
Keywords: HPLC